Case report and literature review: endoscopic extended endonasal resection of two cases of giant chondroma - Yingxiao, Cao; Hao, Wang; Shuling, Shang; Xike, Zhang; Qingye, Feng (Frontiers in Surgery, 2025)
BackgroundIntracranial chondromas are exceedingly rare neoplasms, accounting for 0.2% to 0.3% of all intracranial tumors. These tumors predominantly originate from the skull base, particularly at the cartilaginous junctions of the cranial sutures, with the sella turcica being the most common site.Case presentationBetween April 2022 and August 2023, the Department of Neurosurgery at Xingtai People’s Hospital Affiliated to Hebei Medical University treated two cases of giant skull base chondromas using endoscopic extended endonasal resection. Near-total resection was achieved, and postoperative histopathological examination confirmed the diagnosis of chondroma. Both patients recovered well postoperatively.ConclusionSkull base chondromas are deeply seated and often involve extensive regions. Complete surgical resection remains the greatest challenge and the most critical factor influencing prognosis.selecting the appropriate surgical approach and achieving complete endoscopic resection can effectively prevent tumor recurrence and improve patient quality of life.